Selection on oxidative phosphorylation and ribosomal structure as a multigenerational response to ocean acidification in the common copepod Pseudocalanus acuspes. (23rd November 2015) - De Wit, Pierre; Dupont, Sam; Thor, Peter
Abstract: Ocean acidification is expected to have dramatic impacts on oceanic ecosystems, yet surprisingly few studies currently examine long‐term adaptive and plastic responses of marine invertebrates to p CO2 stress. Here, we exposed populations of the common copepod Pseudocalanus acuspes to three p CO2 regimes (400, 900, and 1550 μatm) for two generations, after which we conducted a reciprocal transplant experiment. A de novo transcriptome was assembled, annotated, and gene expression data revealed that genes involved in RNA transcription were strongly down‐regulated in populations with long‐term exposure to a high p CO2 environment, even after transplantation back to control levels. In addition, 747 000 SNPs were identified, out of which 1513 showed consistent changes in nucleotide frequency between replicates of control and high p CO2 populations. Functions involving RNA transcription and ribosomal function, as well as ion transport and oxidative phosphorylation, were highly overrepresented. We thus conclude that p CO2 stress appears to impose selection in copepods on RNA synthesis and translation, possibly modulated by helicase expression. Using a physiological hypothesis‐testing strategy to mine gene expression data, we herein increase the power to detect cellular targets of ocean acidification. This novel approach seems promising for future studies of effects of environmental changes in ecologically important nonmodel organisms.